Reduction of dislocation densities in single crystal CVD diamond by confinement in the lateral sector - Boussadi, A.; Tallaire, A.; Kasu, M.; Barjon, J.; Achard, J. (Diamond and related materials, 2018)
The use of diamond as a semiconductor material in power electronics applications is held back by the presence of vertical threading dislocations that are believed to deteriorate device performance. Reducing their occurrence in single crystal diamond is therefore crucial. Recently we found that thick CVD diamond grown on the inclined plane of a pyramidal-shape substrate can lead to dislocation bending from a [001] to a [110] direction (Tallaire et al., 2013a [1]). In this work we further explore this strategy for the growth of thick crystals with low dislocation density. It is shown that the boundary angle between inclined lateral and top faces plays a critical role in preserving bent dislocations during the entire growth run. Indeed under well-chosen growth conditions, a boundary angle of at least 45° ensures that dislocations never intercept the top face and are confined in a lateral sector. We eventually show clear evidence of dislocation density reduction in the crystal using this approach. [Display omitted] •Growth of thick (100)-oriented single crystal CVD diamond with low dislocation density on (100) pyramidal shape substrate.•Evolution of pyramidal shape as function of boron and nitrogen impurities concentration in the gas phase and power/pressure values.•Evolution of growth sector boundary angle and control of direction propagation of dislocation.•Confinement of dislocations in lateral sectors during CVD diamond growth.